THE INFLUENCE OF EDUCATION IN DETERMINING POLITICAL CHOICES IN THE 2024 PRESIDENTIAL GENERAL ELECTION IN CENTRAL KALIMANTAN PROVINCE - Karya, Betty; Junaidi, Kur (JURNAL SOCIOPOLITICO, 2025)
Education plays an important role in shaping an individual's political choices. In the context of the 2024 Presidential Election in Central Kalimantan Province, this research aims to explore how people's level of education influences their political decisions. Through statistical data analysis and case studies, this journal will reveal the relationship between education and political choices, as well as its implications for election results. By using qualitative and quantitative approaches, this research is expected to provide deeper insight into political dynamics in Central Kalimantan.